Impact of Unequal Distribution of Canal Water on Farm Produce: A Case Study Matli Taluka - Zareen Khan Rind,; Ghulam Ali Jariko,; Shahabuddin Mughal ,; Ghazala Umer Baghal, (Journal of Basic & Applied Sciences, 2018)
This study seeks to investigate to identify the impact of shortage of water on the tail, end areas of the irrigation network. For the research study 320 respondents were randomly selected and nearly 107 from each category that is large medium and small farmer’s respondent. The sample further stratified respondents from all three reaches that is head middle and tail of main semi-irrigation channels and on the water courses level as well to capture the authentic picture of the water availability on each level of irrigation system. The observation of the study and data collected revealed that farmers on the head reaches benefit more from the supply of water from crop production compare to middle and tail reaches and middle reaches have more opportunity of having better irrigation water compare to the tail reaches however, the more sufferers are the tail reach farmers who get less water from crop production. Consequently, this situation cause’s absolute poverty to the farmers on the tail reaches of the irrigation water supply channels.